A synopsis of Cousinia sect. Pseudactinia (Cardueae, Asteraceae) including a new species from NE Iran - Mehregan, Iraj; Assadi, Mostafa (Phytotaxa, 2016)
A synopsis of Cousinia sect. Pseudactinia is given. The section in its new circumscription includes five perennial species, i.e. C. amicorum, C. edmondsonii, C. glochidiata, C. oreodoxa, and a new species C. joharchii which is described from N slopes of Mt. Shahvar in province of Semnan (NE Iran). Cousinia apiculata is reduced as synonym to C. glochidiata. An identification key to all species of the section is also provided.